18.8k views
4 votes
What is the solution to the following equation?
2x^2-3x+2=0 ​

User Gilletty
by
5.1k points

2 Answers

4 votes

Answer:


x = (3 +/- i √(7) )/(4)

Explanation:


2x^(2) -3x + 2 = 0

a =2 b = -3 c = 2. Substitute these into the quadratic formula
x = \frac{-b +/- \sqrt{b^(2)- 4ac} }{2a}.


x = \frac{-(-3)+/- \sqrt{(-3)^(2) - 4(2*2)} }{2(2)} Simplify.


x = \frac{3+/-\sqrt{(9)^(2) - 4(4) } }{4} Keep simplifying...


x = (3+/-√(9-16) )/(4) Simplify again...


x = (3 +/-√(-7) )/(4) There will be an imaginary number because the number under the
\sqrt{} is negative, so


x = (3+/-i√(7) )/(4)

User Xudre
by
5.3k points
3 votes

Answer:

x=(3+sqrt(7)*i)/4, (3-sqrt(7)*i)/4.

Explanation:

Apply the quadratic formula.

User Jimifiki
by
5.1k points